PELAKSANAAN TUGAS SUPERVISOR HOUSEKEEPING DALAM PENGAWASAN ROOM BOY HOTEL PESONNA PEKANBARU - Indro Susilo; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Implementation Supervisor is someone who is given the position on control,oversee, and be held responsible for his or her subordinates. The presentace of asupervisor also optimizes the productivity of an employee in accordance to the standaroperational procedure. The aim of this research is to understand the obstacles ahousekeeping supervisor at pesonna hotel pekanbaru faces is oversaaing the hotel’sRoom Boy and how he she antivipates it. The methot of research to be used is thequalitative method, the informant that will be used is a housekeeping supervisor andfive othe employees, specifically the Room Boys, the data collection will be done by wayof interview, observation and documentation. The result of this reseach will uncoverthe challenges a supervisor faces in overseeing Room Boys at Pesonna HotelPekanbaru, it will also uncover the mitigation prepared.Keywords: Imlementation Supervisor, Housekeeping Departement, Room Boy